Input Demand and the Short- and Long-Run Employment Thresholds. An Empirical Analysis for the German Manufacturing Sector - Gebhard Flaig; Horst Rottmann (Center for Economic Studies and ifo Institute (CESifo), 2000)
The concept of the employment threshold plays an important role in the public discussion of unemployment. The employment threshol d is defined as that growth rate of output which is necessary to keep employment constant despite the continuous rise in labour productivity. It is related to the Okun coefficient which describes the relationship between the changes of output and unemploy ment. Many contributions to this debate give the impression that the employment threshold is more or less a structural characteristic which remains constant over time. In this paper we derive short- and long-run employment thresholds from an input demand sy stem and show empirically that they depend on factor prices. A moderate wage policy leads to a reduction of the output growth which is necessary for an increase in employment.
Keywords: 330; Okun's Law; employment threshold; productivity